The effect of inquiry-based learning assisted by story-map on students' spatial thinking skills in seismic studies - Purwanto, Purwanto; Asyarifah, Runing Fikriyah; Sahrina, Alfi; Astuti, Ike Sari; Ibrahim, Mohd Hairy (Universitas Negeri Yogyakarta, 2024)
Fundamental changes in 21st-century learning impact geography learning, which must be balanced with students' spatial thinking ability. This ability is a core ability in geography that students must have in the process and results of learning geography. The inquiry-based learning model, with the help of story maps, is an alternative way to stimulate students to develop the ability to think spatially. This study aims to determine how applying inquiry-based learning using story maps affects spatial thinking abilities, especially in seismic studies. The method used in this study was an experiment with a quasi-experimental type using a posttest-only control group design. Data collection techniques in this study used a test in the form of posttest and observation to observe the learning process during the study. Posttest data were obtained from 66 class X students of SMAN 1 Genteng, divided into control and experimental classes. The data were analyzed using the classic assumption regression test, and further hypothesis analysis was done using a simple linear regression test. The results of this study show an influence of the application of story map-assisted inquiry-based learning on students' spatial thinking abilities at 16.7%, as assessed by R Square. In addition, the findings in this study show that the average scores for each indicator of thinking ability are diverse. The highest average in both control and experimental classes, namely analogy and transition indicators. While the lowest average in both courses is the comparison indicator.